Uniformidade de aplicação de água e fertirrigação em um sistema modular de irrigação por gotejamento - Borssoi, Adilson Luiz (2009)
Irrigation by gravity is a technique applied to familiar farming that has been spread in Brazil. It is put into practice in social programs of some States or sold directly to producers. These sets of irrigation management have simplified and low costs, which improve the agricultural production, raise prospective life in countryside and therefore settle the small producer down on his farm. Based on this, the present study evaluated the coefficient of distribution uniformity (CDU) and coefficient of variation (CV), compared two methodologies to evaluate drip irrigation systems and determined the best height to set a tank that will provide pressure for the correct operation of all irrigation by gravity. The study was carried out at the Experimental Center of Agricultural Engineering of UNIOESTE, in Cascavel, Paraná. A set of irrigation, NetafimTM, was evaluated for familiar farming. It consists of a 1.7 Lh-1 drip tube as micro drip, screen filter, 12 mm connectors and a 20 mm diameter derivation line of polyethylene. Two experiments were carried out (irrigation and fertirrigation) and put under four pressures (1.2, 1.4, 1.6 and 1.8 mca) in a completely randomized design, according to two methodologies for flow collection: one proposed by Keller & Karmeli (1975) and the other by Deniculi et al. (1980), with 16 and 32 drippers that were evaluated respectively. Twenty flow collections were done with three replications, during 110 days. In the experiment fertirrigation, the first one was diluted directly into a 200 L tank, which supplied another 30 L container, adapted to control the pressurization according to its height. Fertilization was simulated for bean crop using urea, potassium chloride (KCl) and monoammonium phosphate (MAP). Data were statistically processed by comparison among treatments and each methodology, while the irrigation set was classified by the pattern by ASAE. For fertirrigation, the best pressure was 1.6 mca, classified as excellent for CDU (91.03%) and marginal for CV (7.47%). For the irrigation treatment, the best pressure was 1.6 mca, classified as excellent for CDU (91.2%) and marginal for CV (7.68%). Deniculi et al. (1980) methodology was more reliable for the evaluation of drip systems, since it evaluates a larger number of drippers. Treatments based on fertirrigation did not suffer any loss of distribution uniformity and can be adopted for such set.